2013
DOI: 10.1177/0004563213506412
|View full text |Cite
|
Sign up to set email alerts
|

Salivary testosterone measurement by liquid chromatography tandem mass spectrometry in adult males and females

Abstract: Background: Salivary testosterone (Sal-T) may be a useful surrogate of serum free testosterone. The study aims were to use a novel liquid chromatography tandem mass spectrometry (LC-MS/MS) assay to determine whether Sal-T concentrations accurately reflect Sal-T concentrations in both sexes and to investigate practical aspects of sample collection. Methods: Saliva and serum samples were collected in 104 male and 91 female subjects. A more sensitive LC-MS/MS assay was developed to enable Sal-T quantitation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
92
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 19 publications
9
92
0
Order By: Relevance
“…LC-MS/MS is now the gold standard for the measurement of steroid hormone levels since it has improved specificity and sensitivity [11,12]. Salivary T has previously been measured by LC-MS/MS across the full adult range in males, and it correlates significantly with serum free T [13]. Results expressed as mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS/MS is now the gold standard for the measurement of steroid hormone levels since it has improved specificity and sensitivity [11,12]. Salivary T has previously been measured by LC-MS/MS across the full adult range in males, and it correlates significantly with serum free T [13]. Results expressed as mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that Sal-T can be reliably and accurately measured by a highly sensitive and specific liquid chromatography–tandem mass spectrometry method (16). In a validation study comparing samples from the same individuals, we found that Sal-T in adult men and women correlated more strongly with calculated serum free-T than serum total-T (17) and was also unaffected by variations in sex hormone-binding globulin (SHBG) (18). Fiers at al (19) confirmed the good correlation in both men and women between Sal-T and serum free-T measured by equilibrium dialysis but there was a significant systematic positive bias in women, which may reflect the influence of salivary protein binding on the lower female concentrations of Sal-T.…”
mentioning
confidence: 94%
“…An UHPLC-MS/MS method for direct quantification of two T metabolites (3a-glucuronide-6b-hydroxyandrosterone and 3a-glucuronide-6b-hydroxyetiocholanolone) was developed and validated by Pozo's group [54] and this was accomplished with an UHPLC-MS/MS method because three interfering compounds were noted during GC-MS/MS analysis with the most intense ion transitions. For the free T or its conjugates and other EAAS after hydrolysis, LC-MS/MS methods are available for quantification [57] in urine, plasma and serum [58][59][60][61], hair [62,63] and saliva [64]. Fabregat's group [57] described a rapid, accurate and sensitive LC-MS/MS method for measuring T fractions and its metabolites released under basic conditions.…”
Section: Testosterone and Endogenous Androgenic Anabolic Steroidsmentioning
confidence: 99%